Students' Perception of Video Posted on Social Networks to Improve English Speaking Skills in EFL Students - Widia Wati; Iis Sujarwati (Sakura Digital Nusantara, 2026)
The objective of this study is to investigate students’ perception towards the implementation of video posted on social networks in learning speaking and its experiences. This research used Mixed method. 30 students were used in the population. However, the sample of this research was thirty students of English Education Department, Muhammadiyah University of Bengkulu, Indonesia. Thus, total sampling was used by the sampling technique. To answer the research questions, the study employed a questionnaire and interviews. The questionnaire was administered to thirty students, while only five students participated in the interviews. The data were analyzed both quantitatively and qualitatively. For the quantitative analysis, simple calculations were used to determine percentages and mean scores. For the qualitative analysis, coding was applied to the interview data. The findings revealed that students responded positively to the implementation of videos shared on social media in the English speaking class. Interview results also indicated that social media videos provided engaging learning experiences and increased students’ willingness to practice speaking English. Therefore, videos posted on social media platforms can be considered an effective supplementary medium for improving English speaking skills among EFL students.